2018
DOI: 10.1684/ecn.2018.0410
|View full text |Cite
|
Sign up to set email alerts
|

Role of IL-18 in transplant biology

Abstract: Since pro-inflammatory cytokine IL-18 and its receptor (IL-18R) are closely involved in regulating both adaptive and innate immune responses, it is conceivable that they might play an important role in organ transplantation. IL-18 can stimulate lymphocytes to produce the IFN-␥ and regulate macrophage activity, thereby increasing the expression of proinflammatory cytokines including IL-1␤, IL-6, CCL4 (macrophage inflammatory protein-1 ␤), CXCL2 (macrophage inflammatory protein-2), and CCL2 (monocyte chemotactic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 25 publications
1
11
1
Order By: Relevance
“…Th17 responses especially Th1 responses (32), decreased significantly after IVIG high dose infusion. The main role of IL-18 is to crucially stimulate lymphocytes to produce the IFN-γ and regulate macrophages activity (32). However, in our study, serum levels decrease of IL-18 was not followed by a significant effect on serum levels of IFN-γ.…”
Section: Discussioncontrasting
confidence: 82%
“…Th17 responses especially Th1 responses (32), decreased significantly after IVIG high dose infusion. The main role of IL-18 is to crucially stimulate lymphocytes to produce the IFN-γ and regulate macrophages activity (32). However, in our study, serum levels decrease of IL-18 was not followed by a significant effect on serum levels of IFN-γ.…”
Section: Discussioncontrasting
confidence: 82%
“…Its function is normally regulated by the presence of the high-affinity molecule IL18BP. For this reason, Liu et al recently proposed to neutralize IL18 with IL18BP for the treatment of immune-mediated conditions, in which injury-associated cytokines are produced, including IFNg and CXCL10 (44). In support to the probable role of macrophages and endothelial damage in the development of GF, recently, IL18 has been also described as potential biomarker and therapeutic target of macrophage activation syndrome/HLH, which shares, as mentioned before, several important features with GF (45).…”
Section: Resultsmentioning
confidence: 99%
“…IL17 is associated with rejection ( 52 55 ). IL17 and IL6 are associated with rejection injury ( 56 58 ), while IL18 induces local cytokines and chemokine expression in the allograft ( 59 , 60 ). Quantitative PCR analysis showed that IL17 expression did not change in autografts but is increased 3.03-fold in the allografts.…”
Section: Resultsmentioning
confidence: 99%